Composite material taking carbide ceramic as reinforcing phase and preparation method thereof
By uniformly distributing carbide ceramic particles in high-temperature alloys, the interface bonding force of high-temperature alloy ceramic composite materials is improved, and the poor stability problem caused by uneven distribution of ceramic particles is solved, and high-temperature performance improvement and resistance in environments above 1273K are achieved The tensile strength is increased.
Patent Information
- Application Number
- CN202411218099.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
AI Technical Summary
The existing high-temperature alloy ceramic composite materials have poor stability in high-temperature environments and the uneven distribution of ceramic particles, which limits the safety and reliability of components and improve performance.
Carbide ceramics (TiC, HfC or NbC) are mixed with powders of CoNiCrW-based high-entropy alloys or NiCrWMo-based entropy alloys. By additive manufacturing processes such as laser selection melting or electron beam selection melting, a uniformly distributed carbide ceramic is formed. Strengthen the phase, improve the interface bonding force between the matrix and carbide ceramics, and enhance the strength and toughness of the composite material.
The high-temperature performance of composite materials in an environment above 1273K has been improved, and the tensile strength has been significantly improved, which has reduced the risk of interface cracking and enhanced the metallurgical quality and temperature resistance of the materials.
Smart Images

Figure CN119114939A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of additive manufacturing, and in particular to a method for preparing a carbide ceramic reinforced high-temperature alloy. Background Art
[0002] At present, in the field of aviation, important heat-resistant parts are mainly made of high-temperature alloys, such as nickel-based alloys, which can withstand temperatures above 750°C. Heat-resistant parts mostly use traditional nickel-based high-temperature alloys, such as GH3625, GH3536, and GH3230, and their long-term working temperature is generally limited to 1173K to 1253K. With continuous research, a cobalt-based high-temperature alloy with the grade GH5188 was developed. It is the alloy with the highest heat resistance among traditional deformable high-temperature alloys, and its long-term service temperature can be close to 1273K.
[0003] With the continuous development of aerospace, the requirements for its manufacturing parts are getting higher and higher. Related research adds nano-scale ceramic particles to high-temperature alloys. Although the performance of the resulting composite materials has been improved, the improvement is limited, and the stability is poor. The distribution of ceramic particles is uneven, and its performance and life are limited, which seriously restricts the safety and reliability of existing components and the improvement of overall performance.
[0004] Therefore, there is an urgent need for a preparation method with process stability and good formability to ensure the high-temperature performance of the resulting composite material. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a method for preparing a carbide ceramic reinforced high-temperature alloy to ensure the high-temperature performance of the obtained composite material and enable it to work in an environment above 1273K for a long time.
[0006] On the one hand, the present invention provides a method for preparing a composite material with carbide ceramic as a reinforcement phase, wherein a high temperature alloy is used as a matrix and carbide ceramic is added to prepare a composite material;
[0007] The following steps are involved:
[0008] S1: first mix carbide ceramic powder and high temperature alloy powder;
[0009] The carbide ceramic is TiC, HfC or NbC; the high temperature alloy is CoNiCrW series high entropy alloy or NiCrWMo series medium entropy alloy; the particle size of the carbide ceramic powder is 40 to 80 microns; the particle size of the high temperature alloy powder is 40 to 90 microns;
[0010] S2: Prepared by additive manufacturing process to obtain a composite material.
[0011] Furthermore, the additive manufacturing is a laser selective melting process, a laser melting deposition process or an electron beam selective melting process.
[0012] Furthermore, when the additive manufacturing is a laser selective melting process, the power of the laser selective melting is 200-300 W, the scanning speed is 1000-1100 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.
[0013] Furthermore, when additive manufacturing is a laser melting deposition process, it includes both single-channel and dual-channel methods. The powder feeding amount of the powder feeding channel is 1600rpm-2000rpm, and the powder carrier gas flow rate is 6L / min-8L / min; the laser power is 600-800W, and the scanning speed is 600-700mm / min.
[0014] Furthermore, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 - 4 mbar, the working voltage is 60kV, the electron beam power is set to 4500-5500W, the thickness of each powder layer is 50μm, and the preheating temperature is 500-600℃.
[0015] Furthermore, the chemical composition of the CoNiCrW series high entropy alloy includes, by mass percentage, C: 0.09-0.11%; Cr: 21.5-22.5%; Ni: 20.5-22.0%; W: 17.1-18.1%; Mn: 0.8-1.0%; La: 0.06-0.08%; B: 0.007-0.010%; Si: 0.3-0.4%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; Pb<0.0005%; Cu<0.01%, Co: balance.
[0016] Furthermore, the chemical composition of the entropy alloy in the NiCrWMo system, in terms of mass percentage, includes C: 0.05-0.10%; Cr: 19.0-23.0%; Co≤6.0%; W: 16.8-18.8%; Mn: 0.3-1.0%; Mo: 0.5-2.5%; Al: 0.2-0.5%; La: 0.01-0.1%; Si: 0.25-0.75%; Fe≤2.0%; B<0.015%; P<0.03%; S<0.015%; O<0.02%; N<0.01%; Ti<0.1%; Cu<0.5%; Ni: balance.
[0017] Furthermore, the carbide ceramic powder is 5 vol.% to 22 vol.%; the high temperature alloy powder is 78 vol.% to 95 vol.%.
[0018] On the other hand, the present invention provides a composite material with carbide ceramic as a reinforcement phase, which is prepared by the preparation method of the present invention.
[0019] Furthermore, at 1273K, the tensile strength is above 177MPa, and at 1373K, the tensile strength is above 93MPa.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] 1. After the high-temperature alloy powder and the carbide ceramic powder are melted by additive manufacturing, the W element in the high-temperature alloy powder quickly diffuses to the surface of the carbide ceramic and forms a thin interface layer, which can ensure the interface bonding force between the matrix and the carbide ceramic phase, thereby improving the compatibility between the high-temperature alloy matrix and the carbide ceramic, effectively reducing the risk of interface cracking, and greatly improving the internal metallurgical quality of the composite material and the product.
[0022] 2. The high-temperature alloy of the present invention is a CoNiCrW series high-entropy alloy or a NiCrWMo series medium-entropy alloy, which is used as a matrix and is ensured to contain a relatively high W element. After additive manufacturing, not only the performance of the matrix is guaranteed, but also the strength of the interface and the composite material is guaranteed.
[0023] 3. The reinforcing phase of the present invention uses ceramic powder of TiC, HfC or NbC, whose particle size is 40 to 80 microns, which is close to the particle size of high-temperature alloy powder of 40 to 90 microns, which can ensure that the ceramic is evenly distributed in the high-temperature alloy, and the obtained composite material has higher strength and toughness.
[0024] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0026] Figure 1 Schematic diagram of TiC particles;
[0027] Figure 2Schematic diagram of spherical powder of NiCrWMo medium entropy alloy;
[0028] Figure 3 This is a scanning electron microscope image of the microstructure of the TiC ceramic particle reinforced composite material;
[0029] Figure 4 This is a dark-field transmission electron microscope photograph of the microstructure of the TiC ceramic particle reinforced composite material. DETAILED DESCRIPTION
[0030] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0031] At present, in the aviation field, high-temperature alloys with grades of GH3625, GH3536, GH3230 or GH5188 are mainly used to prepare heat-resistant parts. The long-term working temperature is generally stable at 1173K~1253K, and can be close to 1273K.
[0032] With the continuous development of aerospace, the requirements for its manufacturing parts are getting higher and higher. Related research adds nano-scale ceramic particles to high-temperature alloys. Although the performance of the resulting composite materials has been improved, the improvement is limited, and the stability is poor. The distribution of ceramic particles is uneven, and its performance and life are limited, which seriously restricts the safety and reliability of existing components and the improvement of overall performance.
[0033] Therefore, the present invention provides a method for preparing a composite material with carbide ceramic as a reinforcement phase, using a high-temperature alloy as a matrix and then adding carbide ceramic to prepare a composite material;
[0034] The following steps are involved:
[0035] S1: first mix carbide ceramic powder and high temperature alloy powder;
[0036] The carbide ceramic is TiC, HfC or NbC; the high temperature alloy is CoNiCrW series high entropy alloy or NiCrWMo series medium entropy alloy; the particle size of the carbide ceramic powder is 40 to 80 microns; the particle size of the high temperature alloy powder is 40 to 90 microns;
[0037] S2: Prepared by additive manufacturing process to obtain a composite material.
[0038] Compared with the prior art, the present invention adopts TiC, HfC or NbC ceramic powder as the reinforcing phase, and its particle size is 40 to 80 microns, which is close to the particle size of 40 to 90 microns of the high-temperature alloy powder, which can ensure that the ceramic is evenly distributed in the high-temperature alloy, and the resulting composite material has high strength and toughness. After the high-temperature alloy powder and the carbide ceramic powder are melted by additive manufacturing, the W element in the high-temperature alloy powder quickly diffuses to the surface of the carbide ceramic and forms a thin interface layer, which can ensure the interface bonding force between the matrix and the carbide ceramic phase, thereby improving the compatibility between the high-temperature alloy matrix and the carbide ceramic, effectively reducing the risk of interface cracking, and greatly improving the internal metallurgical quality of the composite material and the product.
[0039] Specifically, the particle size of the high temperature alloy powder is 40 to 90 microns.
[0040] Specifically, the particle size of the carbide ceramic powder is 40 to 80 microns.
[0041] It should be noted that in the present invention, the high temperature alloy powder is spherical, and its particle size is controlled within the range of 40 to 90 microns; the carbide ceramic powder is quasi-spherical, and its particle size is controlled within the range of 40 to 80 microns.
[0042] When the particle size is within the above range, the powder particle size is more uniform. There are two main benefits to controlling the particle size of the powder. The first is to ensure the uniformity and consistency of the additive manufacturing process, which is beneficial to the layer stacking and melting in the additive manufacturing process, and can ensure that the resulting composite material has high performance and temperature resistance; the second is to ensure the fluidity of the raw materials and the stability of the molten pool. The uniform particle size range makes the powder more fluid in the additive manufacturing equipment and can be evenly stacked, thereby improving the molding quality and surface smoothness.
[0043] However, when the powder exceeds the above-mentioned particle size range, it is easy to lead to a decrease in the forming quality of the composite material, resulting in uneven stacking or unstable melting quality, and reducing the dimensional accuracy and mechanical properties of the composite material.
[0044] Preferably, the particle size of the high temperature alloy powder is 50 to 80 microns.
[0045] More preferably, the particle size of the high temperature alloy powder is 60 to 70 microns.
[0046] Preferably, the particle size of the carbide ceramic powder is 50 to 70 microns.
[0047] More preferably, the particle size of the carbide ceramic powder is 60 to 65 microns.
[0048] Specifically, the carbide ceramic powder includes TiC, HfC or NbC.
[0049] It should be noted that the three carbides TiC, HfC and NbC have good chemical stability and compatibility. Their melting points are as high as 3200℃ (TiC), 3890℃ (HfC) and 3180℃ (NbC), respectively. They have good chemical stability and compatibility with other alloy elements at high temperatures. They can form stable compounds and phases with elements in high-temperature alloys (such as Co, Ni, Cr, etc.), are not easy to decompose or react at high temperatures, and help maintain the stability and performance of composite materials. In addition, TiC, HfC and NbC have good hardness and wear resistance, and can effectively protect the alloy matrix under high temperature and high stress environments, extending the service life of composite materials or parts.
[0050] In addition, the thermal conductivity and thermal expansion coefficient of TiC, HfC and NbC are similar to those of high-temperature alloys, which is beneficial to reduce the stress, deformation and even cracks caused by the mismatch of thermal expansion between the matrix and the ceramic reinforcement phase, thereby improving the stability and reliability of the composite material.
[0051] The carbide ceramic powder of the present invention does not contain carbides such as WC. Although it also has good hardness and wear resistance, WC has poor compatibility with the high-temperature alloy matrix, which may cause adverse chemical reactions or interactions in the matrix, resulting in instability or performance degradation of the composite material. At the same time, the thermal expansion coefficient of WC may not match that of the high-temperature alloy matrix, which may cause cracks or interface peeling problems during thermal cycles, reducing the strength of the composite material.
[0052] Specifically, the additive manufacturing is a laser selective melting process, a laser melting deposition process or an electron beam selective melting process.
[0053] Specifically, when the additive manufacturing is a laser selective melting process, the power of the laser selective melting is 200-300 W, the scanning speed is 1000-1100 mm / s, the scanning interval is 0.11 mm, and the layer thickness is 50 μm.
[0054] Preferably, when the additive manufacturing is a laser selective melting process, the power of the laser selective melting is 250-300 W, the scanning speed is 1000-1100 mm / s, the scanning interval is 0.11 mm, and the layer thickness is 50 μm.
[0055] Preferably, when the additive manufacturing is a laser selective melting process, the power of the laser selective melting is 200-250 W, the scanning speed is 1000-1100 mm / s, the scanning interval is 0.11 mm, and the layer thickness is 50 μm.
[0056] Specifically, when additive manufacturing is a laser melting deposition process, it includes both single-channel and dual-channel methods. The powder feeding amount of the powder feeding channel is 1600rpm-2000rpm, and the powder carrier gas flow rate is 6L / min-8L / min; the laser power is 600-800W, and the scanning speed is 600-700mm / min.
[0057] Preferably, when additive manufacturing is a laser melting deposition process, it includes both single-channel and dual-channel methods, the powder feeding amount of the powder feeding channel is 1600rpm-2000rpm, and the powder carrier gas flow rate is 6L / min-8L / min; the laser power is 700-800W, and the scanning speed is 600-700mm / min.
[0058] Preferably, when additive manufacturing is a laser melting deposition process, it includes both single-channel and dual-channel methods, the powder feeding amount of the powder feeding channel is 1600rpm-2000rpm, and the powder carrier gas flow rate is 6L / min-8L / min; the laser power is 600-700W, and the scanning speed is 600-700mm / min.
[0059] Specifically, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 - 4 mbar, the working voltage is 60kV, the electron beam power is set to 4500-5500W, the thickness of each powder layer is 50μm, and the preheating temperature is 500-600℃.
[0060] Preferably, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 - 4 mbar, the working voltage is 60kV, the electron beam power is set to 5000-5500W, the thickness of each powder layer is 50μm, and the preheating temperature is 500-600℃.
[0061] Preferably, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 - 4 mbar, the working voltage is 60kV, the electron beam power is set to 4500-5000W, the thickness of each powder layer is 50μm, and the preheating temperature is 500-600℃.
[0062] It should be noted that, in the present invention, carbide ceramic powder and CoNiCrW series high entropy alloy powder are weighed according to corresponding volume ratios, and then the two are mixed, and then melted and prepared by an additive manufacturing process to obtain a composite material.
[0063] The present invention generates a uniformly distributed fine carbide ceramic reinforcement phase in the composite material through an additive manufacturing process. The dispersedly distributed carbide ceramic has a good strengthening effect on the high-temperature strength of the composite material, and there are no defects such as micro cracks and holes inside the composite material.
[0064] In addition, through the additive manufacturing process, the W element in the CoNiCrW high-entropy alloy quickly diffuses to the surface of the carbide ceramic and forms a thin interface layer, which ensures the interface bonding force between the CoNiCrW high-entropy alloy matrix and the carbide ceramic phase, thereby improving the compatibility between the CoNiCrW high-entropy alloy matrix and the carbide ceramic, effectively reducing the risk of interface cracking, greatly improving the internal metallurgical quality of the composite material, and being able to produce large-sized temperature-resistant components.
[0065] Specifically, the surface of the carbide ceramic phase has an interface layer, and the interface layer is a tungsten-containing interface layer.
[0066] Specifically, the interface layer comprises a (Ti, W)C compound and has a thickness of 50 to 200 nm.
[0067] Preferably, the thickness of the interface layer is 50-200 nm.
[0068] Specifically, the carbide ceramic powder is dispersed in the composite material.
[0069] It should be noted that dispersed distribution can make carbides evenly distributed in the matrix material, ensure the consistency of the composite material performance, and avoid the situation where the performance of local areas is too low or too high. Carbides dispersed in the composite material can effectively hinder the expansion of cracks, thereby enhancing the strength and toughness of the composite material and improving the overall tensile and compressive properties.
[0070] Specifically, in the present invention, the high temperature alloy may be a CoNiCrW series high entropy alloy or a NiCrWMo series medium entropy alloy.
[0071] When the high-temperature alloy is a CoNiCrW series high-entropy alloy, its chemical composition, by mass percentage, includes C: 0.09-0.11%; Cr: 21.5-22.5%; Ni: 20.5-22.0%; W: 17.1-18.1%; Mn: 0.8-1.0%; La: 0.06-0.08%; B: 0.007-0.010%: Si: 0.3-0.4%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; Pb<0.0005%; Cu<0.01%, Co: balance.
[0072] The CoNiCrW alloy provided in the present invention is a cobalt-based alloy. The mixing entropy value of the alloy can be changed by changing the elements. The mixing entropy value exceeds 1.5R, meets the requirements of high entropy alloys, and is easier to form a solid solution, so that the matrix and the composite material have better stability at high temperatures. The CoNiCrW alloy produces a lattice distortion effect in the structure and a delayed diffusion effect in the kinetics, so that the alloy matrix is strengthened and is conducive to the generation of nano-scale precipitation phases, thereby achieving the improvement of the temperature bearing capacity and mechanical properties of the composite material.
[0073] When the high-temperature alloy is a NiCrWMo medium-entropy alloy, its chemical composition, in terms of mass percentage, includes C: 0.05-0.10%; Cr: 19.0-23.0%; Co≤6.0%; W: 16.8-18.8%; Mn: 0.3-1.0%; Mo: 0.5-2.5%; Al: 0.2-0.5%; La: 0.01-0.1%; Si: 0.25-0.75%; Fe≤2.0%; B<0.015%; P<0.03%; S<0.015%; O<0.02%; N<0.01%; Ti<0.1%; Cu<0.5%; Ni: balance.
[0074] The NiCrWMo alloy provided in the present invention is a nickel-based alloy. The mixing entropy value of the alloy can be changed by changing the elements. The mixing entropy value is 1R-1.5R, which meets the requirements of medium entropy alloys, so that the matrix and the composite material have better stability at high temperatures.
[0075] It should be noted that the W element has an important influence on the high-temperature properties of high-temperature alloys and can significantly improve the high-temperature strength of the alloy. The first is the solid solution strengthening effect. The W element will form a stable solid solution in the alloy lattice. Even at high temperatures, it can hinder the slip and dislocation movement of the lattice, thereby improving the deformation resistance and strength of the alloy; the second is the precipitation strengthening effect. The W element helps to form a small and uniform precipitation phase. Especially under high temperature conditions, these precipitation phases can exist stably and hinder the movement of dislocations and the slip of grains, effectively enhancing the high-temperature strength of the alloy; the third is the grain boundary strengthening effect. The W element can change the grain boundary structure of the alloy and increase the strength of the grain boundary. The strengthened grain boundary can effectively prevent the movement of the grain boundary and the growth of the grain, maintain the microstructural stability of the alloy at high temperatures, and thus improve the high-temperature strength and performance of the alloy and composite materials.
[0076] The present invention strictly controls the chemical composition ratio in the CoNiCrW alloy, especially the W element content is 16.1-18.1%. The W element in the CoNiCrW alloy diffuses, and under the action of the additive manufacturing process, a W-containing interface layer can be formed on the surface of the carbide ceramic, which can improve the bonding force between the CoNiCrW alloy matrix and the carbide ceramic, and ensure the overall performance of the composite material. However, when the W element content is below 16.1%, the W element in the CoNiCrW alloy diffuses, resulting in a decrease in the W content in the matrix, thereby reducing the heat resistance or high temperature strength of the composite material; when the W element content is above 18.1%, harmful phases will be generated, which will eventually lead to a decrease in the overall performance of the composite material.
[0077] The present invention strictly controls the chemical composition ratio in the NiCrWMo alloy, especially the W element content is 16.8-18.8%. The W element in the NiCrWMo alloy diffuses, and under the action of the additive manufacturing process, an interface layer containing W can be formed on the surface of the carbide ceramic, which can improve the bonding force between the NiCrWMo alloy matrix and the carbide ceramic, and ensure the overall performance of the composite material. However, when the W element content is below 16.8%, the W element in the NiCrWMo alloy diffuses, resulting in a decrease in the W content in the matrix, thereby reducing the heat resistance or high temperature strength of the composite material; when the W element content is above 18.8%, harmful phases will be generated, which will eventually lead to a decrease in the overall performance of the composite material.
[0078] Specifically, the carbide ceramic powder is 5 vol.% to 22 vol.%; the high temperature alloy powder is 78 vol.% to 95 vol.%.
[0079] It should be noted that the present invention uses carbide ceramics as the reinforcing phase and a high-temperature alloy as the metal matrix. The composite material is prepared by reinforcing the high-temperature alloy with carbide ceramics. The carbide ceramics and the elements in the high-temperature alloy (such as Co, Ni, Cr, etc.) can form stable compounds and phases. The obtained composite material has high temperature resistance and mechanical properties as a whole.
[0080] In the present invention, it is necessary to control the amount of carbide ceramic powder added, and the content is controlled at 5vol.% to 22vol.%, and the overall effect of the obtained composite material is better. When the content of carbide ceramic powder is lower than 5vol.%, the carbide ceramic content is too low to play a reinforcing role, and the strength of the composite material is not significantly improved; when the content of carbide ceramic powder is higher than 22vol.%, the ceramic content is too high and the brittleness increases rapidly, and the composite material cannot eliminate cracks and is difficult to form. The content of carbide ceramic powder in the present invention can be 5vol.%, 8vol.%, 10vol.%, 13vol.%, 15vol.%, 18vol.%, 20vol.% or 22vol.%.
[0081] Preferably, the content of the carbide ceramic powder is 8 vol.%-20 vol.%.
[0082] More preferably, the content of the carbide ceramic powder is 10 vol.%-18 vol.%.
[0083] Specifically, at 1273K, the tensile strength is above 177MPa, and at 1373K, the tensile strength is above 93MPa.
[0084] Specifically, when the matrix is a CoNiCrW-based high entropy alloy, the tensile strength is above 191 MPa at 1273 K, and the tensile strength is above 118 MPa at 1373 K.
[0085] Specifically, when the matrix is a NiCrWMo medium entropy alloy, the tensile strength is above 177 MPa at 1273 K, and the tensile strength is above 93 MPa at 1373 K.
[0086] In order to more clearly describe the present invention, the following examples and comparative examples are provided. Figure 1-4 Further explanation.
[0087] Example 1
[0088] Preparation of CoNiCrW high entropy alloy-based composite materials: comprising the following steps:
[0089] S1: CoNiCrW series high entropy alloy powder and carbide ceramic powder are mixed according to corresponding volume ratios, wherein the carbide ceramic powder accounts for 15 vol.% of the total volume; the CoNiCrW series high entropy alloy powder is spherical, and its particle size is controlled within the range of 60 microns; the carbide ceramic powder is quasi-spherical, and its particle size is controlled within the range of 60 microns;
[0090] The chemical composition of CoNiCrW high entropy alloy is C: 0.10%; Cr: 22.1%; Ni: 21.5%; W: 17.3%; Mn: 0.95%; La: 0.07%; B: 0.008%; Si: 0.35%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; Pb: 0.0004%; Cu: 0.005%; Co: balance;
[0091] The carbide ceramic powder is TiC;
[0092] S2: Spread the mixed powder, and then use laser selective melting for additive manufacturing, the power of the laser selective melting is 280W, the scanning speed is 1000mm / s, the scanning interval is 0.11mm, and the layer thickness is 50μm; obtain a composite material.
[0093] Example 2
[0094] The preparation process of Example 2 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Example 2 is C: 0.07%; Cr: 20.5%; Ni: 19.5%; W: 16.1%; Mn: 0.6%; La: 0.04%; B: 0.005%; Si: 0.2%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; Pb: 0.0004%; Cu: 0.005%; Co: balance;
[0095] Example 3
[0096] The preparation process of Example 3 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Example 3 is C: 0.13%; Cr: 23.5%; Ni: 23.0%; W: 18.1%; Mn: 1.2%; La: 0.10%; B: 0.012%; Si: 0.5%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; Pb: 0.0004%; Cu: 0.005%; Co: balance;
[0097] Examples 4-9, Comparative Examples 1-3
[0098] The preparation processes of Examples 4-9 and Comparative Examples 1-3 are substantially the same as those of Example 1, except for the differences shown in Table 1.
[0099] Table 1 Parameters of Examples 4-9, Comparative Examples 1-3 and Example 1
[0100]
[0101]
[0102] Comparative Example 4
[0103] The preparation process of Comparative Example 4 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Comparative Example 4 is W: 15.1%.
[0104] Comparative Example 5
[0105] The preparation process of Comparative Example 5 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Comparative Example 5 is W: 19.1%.
[0106] Comparative Example 6
[0107] The preparation process of Comparative Example 6 is substantially the same as that of Example 1, except that Comparative Example 6 is a cobalt-based high-temperature alloy GH5188 and does not contain carbide ceramics.
[0108] Performance Testing
[0109] The above-mentioned Examples 1-9 and Comparative Examples 1-6 were subjected to performance tests, mainly including tensile strength and elongation at room temperature, high temperature 1273K and 1373K. The test results are shown in Table 2.
[0110] Table 2 Performance test results
[0111]
[0112]
[0113] It can be seen from Examples 1-9 and Comparative Examples 1-6 and Table 2 that when the technical solutions provided in Examples 1-9 of the present invention are adopted, the obtained composite materials have higher tensile strength and toughness. After performance testing, the hardness at room temperature is above 36.7HRC; at 1273K, the tensile strength is above 191MPa, and at 1373K, the tensile strength is above 118MPa.
[0114] Examples 10-14, Comparative Examples 7-8
[0115] Example 10
[0116] The preparation process of Example 10 is substantially the same as that of Example 1, except that in Example 10, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 250 W, the scanning speed is 1000 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.
[0117] Embodiment 11
[0118] The preparation process of Example 11 is substantially the same as that of Example 1, except that in Example 11, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 300 W, the scanning speed is 1100 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.
[0119] Example 12
[0120] The preparation process of Example 12 is substantially the same as that of Example 1, except that a single-channel powder feeding method is adopted in Example 12, and the mixed powder of CoNiCrW high entropy alloy and TiC is respectively loaded into a powder feeding channel, the powder feeding amount of the powder feeding channel is 2000rpm, and the powder carrier gas flow rate is 7L / min; the power of laser melting deposition is 700W, and the scanning speed is 600mm / min.
[0121] Embodiment 13
[0122] The preparation process of Example 13 is substantially the same as that of Example 1, except that in Example 13, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 5000W, the thickness of each powder layer is 50μm, and the preheating temperature is 500℃.
[0123] Embodiment 14
[0124] The preparation process of Example 14 is substantially the same as that of Example 1, except that in Example 14, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 5500W, the thickness of each powder layer is 50μm, and the preheating temperature is 600℃.
[0125] Comparative Example 7
[0126] The preparation process of Comparative Example 7 is substantially the same as that of Example 1, except that in Comparative Example 7, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 350 W, the scanning speed is 1500 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.
[0127] Comparative Example 8
[0128] The preparation process of Comparative Example 8 is substantially the same as that of Example 1, except that in Comparative Example 8, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4mbar, the working voltage is 60kV, the electron beam power is set to 6500W, the thickness of each powder layer is 50μm, and the preheating temperature is 750℃.
[0129] Performance Testing
[0130] The above-mentioned Examples 10-14 and Comparative Examples 7-8 were subjected to performance tests, mainly including tensile strength and toughness at room temperature and high temperature at 1273K and 1373K. The test results are shown in Table 3.
[0131] Table 3 Performance test results
[0132]
[0133] It can be seen from Examples 1, 10-14 and Comparative Examples 7-8 and Table 3 that when the method for preparing the composite material provided by the embodiment of the present invention is adopted, the obtained composite material has high tensile strength and toughness. After performance testing, the hardness at room temperature is above 39.7HRC; at 1273K, the tensile strength is above 209MPa, and at 1373K, the tensile strength is above 120MPa.
[0134] Embodiment 15
[0135] Preparation of NiCrWMo medium entropy alloy-based composite materials: comprising the following steps:
[0136] S1: Mixing NiCrWMo-based medium entropy alloy powder and carbide ceramic powder according to corresponding volume ratios, wherein the carbide ceramic powder accounts for 15 vol.% of the total volume; and the NiCrWMo-based medium entropy alloy powder is spherical, and its particle size is controlled within the range of 60 microns; the carbide ceramic powder is quasi-spherical, and its particle size is controlled within the range of 60 microns;
[0137] C: 0.08%; Cr: 21.5%; Co: 6.0%; W: 17.8%; Mn: 0.55%; Mo: 1.25%; Al: 0.35%; La: 0.05%; Si: 0.4 5%; Fe: 2.0%; B: 0.01%; P: 0.02%; S: 0.01%; O: 0.015%; N: 0.008%; Ti: 0.08%; Cu: 0.4%; Ni: balance.
[0138] The carbide ceramic powder is TiC;
[0139] S2: The mixed powder is spread, and then laser selective melting is used for additive manufacturing. The power of the laser selective melting is 230 W, the scanning speed is 1000 mm / s, the scanning interval is 0.11 mm, and the layer thickness is 50 μm.
[0140] Example 16
[0141] The preparation process of Example 16 is substantially the same as that of Example 15, except that the chemical composition of the entropy alloy in the NiCrWMo system described in Example 16, in terms of mass percentage, includes C: 0.05%; Cr: 19.0%; Co: 6.0%; W: 16.8%; Mn: 0.3%; Mo: 0.5%; Al: 0.2%; La: 0.01%; Si: 0.25%; Fe: 2.0%; B: 0.01%; P: 0.02%; S: 0.01%; O: 0.015%; N: 0.008%; Ti: 0.08%; Cu: 0.4%; Ni: balance.
[0142] Embodiment 17
[0143] The preparation process of Example 17 is substantially the same as that of Example 15, except that the chemical composition of the entropy alloy in the NiCrWMo system described in Example 17, in terms of mass percentage, includes C: 0.10%; Cr: 23.0%; Co: 6.0%; W: 18.8%; Mn: 1.0%; Mo: 2.5%; Al: 0.5%; La: 0.1%; Si: 0.75%; Fe: 2.0%; B: 0.01%; P: 0.02%; S: 0.01%; O: 0.015%; N: 0.008%; Ti: 0.08%; Cu: 0.4%; Ni: balance.
[0144] Examples 18-23, Comparative Examples 9-11
[0145] The preparation processes of Examples 18-23, Comparative Examples 9-11 and Example 15 are substantially the same, and the differences are shown in Table 4.
[0146] Table 4 Parameters of Examples 18-23, Comparative Examples 9-11 and Example 15
[0147]
[0148]
[0149] Comparative Example 12
[0150] The preparation process of Comparative Example 12 is substantially the same as that of Example 15, except that the chemical composition of the NiCrWMo-based entropy alloy in Comparative Example 12 is W: 15.8%.
[0151] Comparative Example 13
[0152] The preparation process of Comparative Example 13 is substantially the same as that of Example 15, except that the chemical composition of the NiCrWMo-based entropy alloy in Comparative Example 13 is W: 19.8%.
[0153] Comparative Example 14
[0154] The preparation process of Comparative Example 14 is substantially the same as that of Example 15, except that Comparative Example 14 is a cobalt-based high-temperature alloy GH3230 and does not contain carbide ceramics.
[0155] Performance Testing
[0156] The above-mentioned Examples 15-23 and Comparative Examples 9-14 were subjected to performance tests, mainly including tensile strength and toughness (elongation) at room temperature, high temperature 1273K and 1373K. The test results are shown in Table 5.
[0157] Table 5 Performance test results
[0158]
[0159]
[0160] It can be seen from Examples 15-23 and Comparative Examples 9-14 and Table 5 that when the technical solutions provided by Examples 15-23 of the present invention are adopted, the obtained composite materials have higher tensile strength and toughness. After performance testing, the tensile strength is above 177 MPa at 1273 K, and the tensile strength is above 93 MPa at 1373 K.
[0161] Examples 24-28, Comparative Examples 15-16
[0162] Embodiment 24
[0163] The preparation process of Example 24 is substantially the same as that of Example 15, except that in Example 24, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 200 W, the scanning speed is 1000 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.
[0164] Embodiment 25
[0165] The preparation process of Example 25 is substantially the same as that of Example 15, except that in Example 25, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 250 W, the scanning speed is 1100 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.
[0166] Embodiment 26
[0167] The preparation process of Example 26 is substantially the same as that of Example 15, except that in Example 26, a single-channel powder feeding method is adopted, and the mixed powder of NiCrWMo medium entropy alloy and TiC is respectively loaded into one powder feeding channel, the powder feeding amount of the powder feeding channel is 2000rpm, and the powder carrier gas flow rate is 7L / min; the power of laser selective melting is 650W, and the scanning speed is 600mm / min.
[0168] Embodiment 27
[0169] The preparation process of Example 27 is substantially the same as that of Example 15, except that in Example 27, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 4500W, the thickness of each powder layer is 50μm, and the preheating temperature is 500℃.
[0170] Embodiment 28
[0171] The preparation process of Example 28 is substantially the same as that of Example 15, except that in Example 28, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 5000W, the thickness of each powder layer is 50μm, and the preheating temperature is 600℃.
[0172] Comparative Example 15
[0173] The preparation process of Comparative Example 15 is substantially the same as that of Example 15, except that in Comparative Example 15, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 350 W, the scanning speed is 1500 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.
[0174] Comparative Example 16
[0175] The preparation process of Comparative Example 16 is substantially the same as that of Example 15, except that in Comparative Example 16, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 6500W, the thickness of each powder layer is 50μm, and the preheating temperature is 750℃.
[0176] Performance Testing
[0177] The above Examples 24-28 and Comparative Examples 15-16 were subjected to performance tests, mainly including tensile strength and toughness at room temperature, high temperature 1273K and 1373K. The test results are shown in Table 6.
[0178] Table 6 Performance test results
[0179]
[0180] From Example 15, Examples 24-28, Comparative Examples 15-16 and Table 6, it can be seen that when the method for preparing the composite material provided by the embodiment of the present invention is adopted, the obtained composite material has higher tensile strength and toughness. After performance testing, the tensile strength is above 191 MPa at 1273 K, and the tensile strength is above 100 MPa at 1373 K.
[0181] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a composite material with carbide ceramic as a reinforcement phase, characterized in that: Composite materials were made by using high temperature alloy as matrix and adding carbide ceramics; The following steps are involved: S1: first mix carbide ceramic powder and high temperature alloy powder; The carbide ceramic is TiC, HfC or NbC; the high temperature alloy is CoNiCrW series high entropy alloy or NiCrWMo series medium entropy alloy; the particle size of the carbide ceramic powder is 40 to 80 microns; the particle size of the high temperature alloy powder is 40 to 90 microns; S2: Prepared by additive manufacturing process to obtain a composite material.
2. The method for preparing a composite material with carbide ceramic as a reinforcement phase according to claim 1, characterized in that: The additive manufacturing is a laser selective melting process, a laser melting deposition process or an electron beam selective melting process.
3. The method for preparing a composite material with carbide ceramic as a reinforcement phase according to claim 2, characterized in that: When the additive manufacturing is a laser selective melting process, the power of the laser selective melting is 200-300 W, the scanning speed is 1000-1100 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.
4. The method for preparing a composite material with carbide ceramic as a reinforcement phase according to claim 2, characterized in that: When additive manufacturing is a laser melting deposition process, it includes both single-channel and dual-channel methods. The powder feeding amount of the powder feeding channel is 1600rpm-2000rpm, and the powder carrier gas flow rate is 6L / min-8L / min; the laser power is 600-800W, and the scanning speed is 600-700mm / min.
5. The method for preparing a composite material with carbide ceramic as a reinforcement phase according to claim 2, characterized in that: When additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 4500-5500W, the thickness of each powder layer is 50μm, and the preheating temperature is 500-600℃.
6. The method for preparing a composite material with carbide ceramic as a reinforcement phase according to claim 1, characterized in that: The chemical composition of the CoNiCrW series high entropy alloy includes, by mass percentage, C: 0.09-0.11%; Cr: 21.5-22.5%; Ni: 20.5-22.0%; W: 17.1~18.1%; Mn: 0.8~1.0%; La: 0.06~0.08%; B: 0.007~0.010%: Si: 0.3~0.4%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; Pb<0.0005%; Cu<0.01%, Co: balance.
7. The method for preparing a composite material with carbide ceramic as a reinforcement phase according to claim 1, characterized in that: The chemical composition of the NiCrWMo-based entropy alloy includes, by mass percentage, C: 0.05-0.10%; Cr: 19.0-23.0%; Co≤6.0%; W: 16.8~18.8%; Mn: 0.3~1.0%; Mo: 0.5-2.5%; Al:0.2~0.5%; La: 0.01~0.1%; Si: 0.25~0.75%; Fe≤2.0%; B<0.015%; P<0.03%; S<0.015%; O<0.02%; N<0.01%; Ti<0.1%; Cu<0.5%; Ni: balance.
8. The method for preparing a composite material with carbide ceramic as a reinforcement phase according to claim 1, characterized in that: The carbide ceramic powder is 5 vol.% to 22 vol.%; the high temperature alloy powder is 78 vol.% to 95 vol.%.
9. A composite material with carbide ceramic as a reinforcement phase, characterized in that: The method is prepared by any one of claims 1 to 8.
10. The composite material with carbide ceramic as reinforcement phase according to claim 9, characterized in that: At 1273K, the tensile strength is above 177MPa, and at 1373K, the tensile strength is above 93MPa.
Citation Information
Cited By
NiCrWMo-series medium-entropy alloy-based composite material as well as preparation method and application thereof
CN118854123A
TiC particle reinforced CoNiCrW series high-entropy alloy composite material as well as preparation method and application of TiC particle reinforced CoNiCrW series high-entropy alloy composite material
CN119243015A
High-entropy alloy-based composite material and preparation method thereof
CN121535186A
A high-entropy alloy-based composite material and its preparation method
CN121535186B
Composite ceramic particle reinforced high-entropy alloy-based composite material and preparation method thereof
CN121538543A
